Blogging, craft culture, and women empowerment - Manosevitch, Idit (Cogent social sciences, 2017)
The study presents an analysis of the development process that women crafters underwent who began blogging as a hobby and gradually turned their crafts into blog-supported small businesses. The analysis demonstrates the role of sharing via blogging as a driving mechanism for community building and empowerment for economic and personal development. Taking a grounded theory approach, our analysis is based on data collected from semi-structured interviews with top craft bloggers in the local blogosphere. We discuss the findings in light of work on the impact of network technologies on individuals’ and markets.